A single LED based indoor visible light positioning system using smartphone camera and motion sensor - Xu, Han (2018)
With the increasing demand for indoor navigation and positioning, indoor positioning technology is in great demand in recent years. The frequent indoor positioning solutions and schemes mostly are based on Wi-Fi, Bluetooth, RFID and UWB techniques, which have different kinds of deficiencies, for instance, system instability (Wi-Fi, Infra-Red), low accuracy (Wi-Fi, Bluetooth), high hardware complexity (UWB), long response time etc. The widespread use of white LEDs for illumination provides the foundation to establish an indoor positioning system with a simple erection, accurate localization and flexible working environment. And with the rapid development of smartphone, the computing power of smartphone achieved a tremendous progress which satisfies the computing requirement of the real-time indoor positioning system. Also, with the orientation data from Motion Sensor, make a single LED indoor positioning system feasible. Compared to multiple LEDs visible light indoor positioning system, a single LED with motion sensor indoor positioning system has less computation and fewer number of hardware, which means more efficient and convenient and do not have the above deficiencies.